Methodological support of the products competitiveness estimation - Верясова, Г. М. (ХНУРЕ, 2013)
Under this investigation the approach is based on calculating the integral index of product competitiveness has been chosen. Methodology for integrated assessment of enterprise’s product competitiveness allows a direct quantitative comparison of performance indicators, grouped into two groups. Competitiveness is determined by qualitative and economic characteristics – products features that are considered by consumers under their direct relevance to theirs needs.
Keywords: integral index of product competitiveness; competitiveness